2001
DOI: 10.1007/s12110-001-1001-2
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and relationship jealousy

Abstract: The relation between sex hormones and responses to partner infidelity was explored in two studies reported here. The first confirmed the standard sex difference in relationship jealousy, that males (n = 133) are relatively more distressed by a partner's sexual infidelity and females (n=159) by a partner's emotional infidelity. The study also revealed that females using hormone-based birth control (n = 61) tended more toward sexual jealousy than did other females, and reported more intense affective responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 33 publications
(41 reference statements)
4
33
1
2
Order By: Relevance
“…In line with our own data, these cyclical shifts were found to be diminished in women using HC (Cobey et al, 2013;Little et al, 2013). In a natural setting, several partner-related activities such as massage (Morhenn et al, 2012) or coitus (Carmichael et al, 1994) elicit the release of OXT, and a decrease in OXT effectiveness could explain why HC users report reduced sexual functioning (Wallwiener et al, 2010) and increased sexual jealousy (Geary et al, 2001). In fact, OXT has been found to increase the intensity of orgasm and contentment after copulation (Behnia et al, 2014) and to reduce arousal induced by the imagination of sexual infidelity (Preckel et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In line with our own data, these cyclical shifts were found to be diminished in women using HC (Cobey et al, 2013;Little et al, 2013). In a natural setting, several partner-related activities such as massage (Morhenn et al, 2012) or coitus (Carmichael et al, 1994) elicit the release of OXT, and a decrease in OXT effectiveness could explain why HC users report reduced sexual functioning (Wallwiener et al, 2010) and increased sexual jealousy (Geary et al, 2001). In fact, OXT has been found to increase the intensity of orgasm and contentment after copulation (Behnia et al, 2014) and to reduce arousal induced by the imagination of sexual infidelity (Preckel et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, millions of women around the world use steroidbased hormonal contraception (HC) as an effective way of birthcontrol (Alkema et al, 2013). Importantly, HC use alters women's pair-bonding behavior, evident in decreased attractiveness ratings of masculine faces (Little et al, 2013), reduced neural response to the expectation of erotic stimuli (Abler et al, 2013), a preference shift towards olfactory cues of genetic similarity (Roberts et al, 2008) and increased sexual jealousy (Geary et al, 2001). Furthermore, women who use HC while choosing partners are more likely to initiate an eventual separation (Roberts et al, 2012) and wives who discontinue HC use tend to be less satisfied with marriage if they perceive their husband's face to be less attractive (Russell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, none of our analyses revealed the positive effects of estradiol that would have been predicted by previous work linking jealousy to estrogen dose in hormonal contraceptives (Cobey et al, 2011) or differences among women in their salivary estradiol (Geary et al, 2001). Importantly, that testosterone had a positive effect on women's reported intrasexual competitiveness, but not reported jealousy, indicates that the effect of testosterone on reported intrasexual competitiveness is not simply an artifact of a possible general response bias, whereby testosterone may have made women more willing to use extreme points on response scales.…”
Section: Hahn 15contrasting
confidence: 91%
“…By contrast with this finding for intrasexual competitiveness and testosterone, we found no evidence that relationship jealousy tracked changes in women's hormone levels. These results support previous speculation that testosterone plays a key role in regulating women's intrasexual competitiveness (Cobey et al, 2013), but calls into question the suggested role of estradiol in women's relationship jealousy (Cobey et al, 2011;Geary et al, 2001). While previous research on changes in women's intrasexual competitiveness has highlighted links with estimated fertility (Durante et al, 2008(Durante et al, , 2011Fisher, 2004;Haselton et al, 2007;Lucas & Koff, 2013;Vukovic et al, 2009), our study is the first to demonstrate correlated changes in intrasexual competitiveness and natural variation in women's testosterone levels.…”
Section: Hahn 15supporting
confidence: 87%
See 1 more Smart Citation